Pemanfaatan Teknologi Blockchain untuk Meningkatkan Efisiensi dan Efektivitas Sistem Perpajakan: Tinjauan Literatur Sistematik - Hindayani, Novia (Politeknik Raflesia Press, 2024)
This study aims to determine how the factors that influence the successful implementation of blockchain in the tax system through a literature review of 14 samples of international journal articles from 2019-2024. The results of the study show that most publications increase in 2024, namely 4 articles. China and Indonesian is the most researched country. The factors that influence the successful implementation of blockchain in tax system are divided into 5 factors, namely belief & trust, government policy, infrastructure, human resource capabilities and ease of use. This research contributes to the development of knowledge about blockchain in tax systems worldwide. Researchers can investigate empirically the factors identified as confirmation of research, and further researchers can also expand their research area using other models. The findings are obtained from the review literature, so more in-depth testing is needed through the interview or questionnaire method.